2004
DOI: 10.1023/b:ddas.0000011596.33237.5c
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder Contractility in Liver Cirrhosis: Comparative Study in Patients with and Without Gallbladder Stones

Abstract: An increased prevalence of gallstones was demonstrated in patients with liver cirhosis, higher in the advanced stages of the disease. Some studies have found impaired emptying of the gallbladder in cirrhotic patients. Our aim here was to investigate gallbladder emptying in cirrhotic patients with and without gallstones to find out whether emptying is further impaired in the presence of gallstones. The study group comprised 24 patients with liver cirrhosis and gallstones, 8 in each Child class. The controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 27 publications
5
25
0
Order By: Relevance
“…According to the statistical data, the average total number of registered patients was 1500 patient per year, and the prevalence of cholelithiasis was 40 %in CLD patients in the study of Acalovschi et al [8] at confidence interval 95%, and the power was 80%. Our study included 131patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to the statistical data, the average total number of registered patients was 1500 patient per year, and the prevalence of cholelithiasis was 40 %in CLD patients in the study of Acalovschi et al [8] at confidence interval 95%, and the power was 80%. Our study included 131patients.…”
Section: Discussionmentioning
confidence: 96%
“…Over time, the crystals grow, aggregate, and fuse to form macroscopic stones [7]. Moreover, the increase in gall bladder wall thickness by hyperemia, edema, decreased contractility or impaired gallbladder emptying contributes to gallstone formation [8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, there has not been any model based on contractility used for assessing very severe (Grade 1), moderately severe (Grade 2) and mild (Grade 3) gallbladder diseases even though several dynamic studies (Ugwu b ,et al, 2007, Pons, et al, 2003, Siegel et al, 2000,Cay et al, 2006, Acalovschi et al, 2004, Guliter et al, 2003 have been carried out on the gallbladder. This present study is the first.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the mathematical analysis of minute-by-minute ultrasonography measurements of gallbladder volume variations yields both physiological and pathological insight (Pallota, 2003) Clinicians have in their diagnostic armamentarium a wide range of techniques for the preoperative evaluation of gallbladder, such as physical examination, biochemical examination, gray and colour Doppler ultrasonography, axial computed tomography, scintigraphy and magnetic resonance imaging. Several studies have used ultrasonography to evaluate gallbladder contraction index, GBCI (Ugwu, et al, 2007,Ugwu a ;2006, Pons et al, 2003, Siegel et al,2000, Cay et al, 2006, Acalovschi et al, 2004, Guliter, et al, 2003, but none has come up with a grading pattern for gallbladder diseases. Meanwhile no model for grading has been proposed to assist in the determination of the severity of gallbladder disease, prognosis and treatment algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The risk of cholelithiasis in cirrhotic male patients is much higher than in the healthy male population. Fornari et al proposed cirrhosis of liver as a risk factor for gall stones in males and suggested that high levels of estrogen due to decreased clearance by cirrhotic liver could play a role by an impairment of gallbladder emptying; as observed also in pregnant women.…”
Section: Introductionmentioning
confidence: 99%